Dermatoses in geriatric diabetic patients and its association with socioeconomic condition – A cross-sectional observational study in a tertiary care hospital in Eastern India - Banerjee, Shayeri; Ghosh, Animesh; Rudra, Olympia; Praveen, Pranjal; Naskar, Biswanath; Saha, Jinia (Asian Journal of Medical Sciences, 2023)
Background: Diabetes mellitus can have varied cutaneous manifestations. Aims and Objectives: This study aims to explore the plethora of dermatoses among the geriatric diabetic population and evaluate their association with the socioeconomic conditions of the patients. Materials and Methods: This is a cross-sectional observational study carried out on 300 diabetic patients aged 60 and above in department of dermatology of a tertiary care hospital in Eastern India. Data were collected in a pre-designed proforma, and all findings were recorded. Results: Three hundred diabetic patients aged 60 and above were evaluated; 42% were male, 58% were female. About 61.33% belonged to lower socioeconomic status (SES), 24% to middle, and 14.67% to upper SES. Xerosis (66%) and generalized pruritus (44%) were the most common skin manifestations. Among the infective dermatoses, fungal infections (49.3%) were the most common followed by bacterial (29.3%). There was statistically significant correlation of diabetic dermatoses with SES, female gender, obesity, increased intake of junk food, active smokers for more than 10 years, living singly, sedentary lifestyle, and hypertension. Conclusion: An in-depth knowledge of diabetic dermatoses in the elderly and the role of SES and demographic parameters accounting for their increased prevalence has not been sufficiently studied among the Indian population. This study will shed some light on the same and bring in awareness among the doctors and policymakers alike to enhance the health-care needs of the elderly.